2020
DOI: 10.1177/1747493020967224
|View full text |Cite
|
Sign up to set email alerts
|

Clinical features of and risk factors for intracranial aneurysms associated with moyamoya disease

Abstract: Background The clinical features of aneurysms associated with moyamoya disease (MMD) and risk factors for the formation and rupture of aneurysms are not well defined. Aims In this study, we retrospectively analyzed clinical data of MMD patients and examined the potential risk factors for the formation and rupture of aneurysms in these patients. Methods The medical records of all MMD patients in our hospital from April 2012 to May 2019 were reviewed. The logistic regression analysis was used to determine the in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 33 publications
0
11
0
1
Order By: Relevance
“…AchA, anterior choroidal artery; F, female; HH, hunt-hess grading; IH, intracerebral hemorrhage; IVH, intraventricular hemorrhage; M, male; MMD, moyamoya disease; mRS, modified Rankin scale. Although some aneurysms in MMD may regress due to a decrease in blood flow or thrombosis, others are likely to present with rupture (23,(27)(28)(29). Aneurysm rupture may be fatal [Figure 7 (case 5 in Table 2)].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…AchA, anterior choroidal artery; F, female; HH, hunt-hess grading; IH, intracerebral hemorrhage; IVH, intraventricular hemorrhage; M, male; MMD, moyamoya disease; mRS, modified Rankin scale. Although some aneurysms in MMD may regress due to a decrease in blood flow or thrombosis, others are likely to present with rupture (23,(27)(28)(29). Aneurysm rupture may be fatal [Figure 7 (case 5 in Table 2)].…”
Section: Discussionmentioning
confidence: 99%
“…Although some aneurysms in MMD may regress due to a decrease in blood flow or thrombosis, others are likely to present with rupture ( 23 , 27 29 ). Aneurysm rupture may be fatal [ Figure 7 (case 5 in Table 2 )].…”
Section: Discussionmentioning
confidence: 99%
“…ICH originated from the abnormal moyamoya vessels due to the developmental functional disorders of vascular endothelial cells ( 29 ). Hemorrhage sites from the posterior circulation have a higher recurrence risk than from the anterior circulation ( 30 ), and the intracranial aneurysm (IA) could increase the hemorrhagic risk for MMD patients ( 31 ). Although they were not identified as risk factors of future strokes, our study found that hemorrhagic-type MMD patients with IA showed relatively higher recurrent stroke risks than those without IA (15.2 vs. 12.0%).…”
Section: Discussionmentioning
confidence: 99%
“…In der Angiografie sollte auch gezielt nach Aneurysmata gesucht werden, da diese in ca. 8 % der Fälle auftreten können [24]. Typischerweise kommt es zu Grenzzoneninfarkten und Kopfschmerzen oder Hirnblutungen.…”
Section: Moyamoya-erkrankung Moyamoya-syndromunclassified